PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING DENGAN MEDIA WORDWALL TERHADAP HASIL BELAJAR SISWA KELAS VIII DI MTsN 1 LAMONGAN - Mohamad Novan Aditya; Luthfiya Fathi Pusposari (Madani : Journal of Social Sciences and Social Science Education, 2024)
The use of inappropriate learning models in the learning process will have an impact on the suboptimal achievement of student learning outcomes. The use of appropriate media has the potential to improve student learning outcomes. This study aims to determine the effect of Game Based Learning model with Wordwall media on student learning outcomes at MTs Negeri 1 Lamongan. This study used a quasi experimen model with pre test post test control group design. The research sample was selected based on porposive sampling, with a total of 32 students each in the experimental class VIII-I (experimental class) and control class VIII-H (control class). Data analysis used mann withney test because the data was not normally distributed. The results showed that there was an effect of using a game-based learning model with wordwall media on student learning outcomes. The game-based learning model with wordwall has a greater influence on learning outcomes when compared to the traditional model. The use of game-based learning model with wordwall media makes students more eager to learn so that it can improve learning outcomes.